Simulação baseada em atores como ferramenta de ensino de organização e arquitetura de computadores - Torres., Andre Luis de Lucena (2012)
The educative informatics has become more present in pedagogical activities. On this new reality, many applications tend to make the knowledge construction a easier tool from the teachers to the students by dynamic methods, exposing multi-branch subjects with no great efforts or unnecessary repetitions. In computing area, the use of applications that facilitate learning is mandatory. Thus, it has been observed that the teaching of some introductory concepts on essential subject used to present an abstraction level that harms the instruction of students of computing courses that have difficulties on hardware related subjects. The use simulators in education have become more present in pedagogical activities. Thus, this work presents the achieved results of an extension developed on a simulation and modeling tool of concurrent systems based in actors, named Ptolemy. The extension was developed to contribute with the teaching-leaning process in the graduation course of Computers Architecture and Organization.